Overview Of The Implementation Of The Code Of Ethics Indonesian Medicine At General Physicians In Private Clinics In Bandung District - Taufan, Ali; Rachmatdinata, Hedi Hendrawan; Negara, Rizqi Krisna (Sean Institute, 2024)
Medical practice in its implementation is expected to contain high ethics and morals for doctors who are at the core of the implementation. The current phenomenon is that many doctors commit deviations and abuse their authority which violates the Indonesian Medical Code of Ethics (KODEKI), which KODEKi should serve as the basis for practice in the world of medicine. The object of research in this research is general practitioners who work at private clinics in Bandung Regency. The method used is qualitative with a descriptive phenomenological study approach. Related to the application of KODEKI values ​​carried out by general practitioners at Regency Private Clinics, the results obtained are 1) the character of godliness or responsibility, namely doctors always adhere to God and make religion the basis for carrying out the responsibilities of the doctor's profession, 2) alturism, namely doctors always prioritizing the interests of patients above personal interests, 3) professional idealism, namely doctors reprimanding colleagues if they make medical mistakes while maintaining the good name of colleagues, 4) patient accountability, namely doctors respecting and listening to patients and not discriminating against patients, 5) integrity scientific, namely doctors always follow developments in medical science through seminars, workshops and further studies and 6) social integrity, namely doctors provide clear information and provide education to improve health. All general practitioner respondents who work in private clinics in Bandung Regency apply KODEKI values.